Strategic marketing management cases / [disket] - 173204 Cravens, David W.; Lamb, Charles W.; Crittenden, Victoria L. (Boston : McGraw-Hill, 1998)
System requirements: IBM PC or compatible, with Windows 3.1 or higher, and Excel 4.0 or higher. Macintosh with MacOS 8 and Excel 5 has been found to work, provided the files are copied to the Mac hard disk first.